Development prospects and possible directions for improvement of the health insurance system in Ukraine - Zagorska, D.; Borovitska, O. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
The article provides an in-depth analysis of modern approaches to the development and improvement of the health insurance system in Ukraine, which is especially relevant in the period of socio-economic changes and the transformation of the national health care financing model. The main goal of the study is to comprehensively highlight the main trends, structural problems and prospects for the stability of medical financing, as well as to formulate realistic and substantiated proposals for the implementation of effective mandatory health insurance (MHI). The work uses multifactor comparative analysis, statistical and structural analytical methods, which allowed us to summarize and assess the main parameters of financial flows in the healthcare sector of Ukraine for the period 2020–2024. The results of the study determined that the share of direct household expenditures on medical care in Ukraine is close to 47%, while state financing does not exceed 4.2% of GDP, which creates serious risks for the foundations of the sustainability of the national healthcare system. A comparison of medical financing in EU countries, such as Germany, France and Poland, was conducted, which made it possible to formulate practical recommendations for the creation of the National Health Insurance Fund, the introduction of transparent tariffs and electronic tools for controlling the use of funds. The importance of solidary distribution of financial risks, improving the quality of medical care and introducing control to reduce corruption risks is emphasized. Thus, the introduction of compulsory health insurance is considered a key factor in ensuring the stability of financing, social justice, reducing the financial burden on citizens and gradually bringing the Ukrainian health care system closer to European standards. The conclusions obtained are of practical importance for the development of state policy in the field of reforming the medical financing system.